Normese en el código de la niñez y adolescencia un marco jurídico que garantice la custodia de las pruebas de adn en el Ecuador - Herrera Loaiza, Rocio del Pilar (2011)
Parenting is both a biological and a legal concept, from a biological point of view, parenthood is the relationship between a father understood as the male parent and their children, commonly referred to in this concept to biological children. Currently, paternity testing is the study of cells of the alleged father and child through DNA tests which reveal whether there are genetic relationship between these two people because of the similarity that must exist between both samples and therefore confirm or deny paternity. ADN is described as a long step spiral molecule contains all the hereditary information and is located inside each cell, formed from the moment of conception and remains the same throughout life. This element is provided by the parents in equal shares, a feature that makes it the ideal tool for analysis and determine paternity. The results of a legal paternity test can be used to prove or disprove the paternity for legal purposes such as child support, custody, and inheritance, and laboratories should provide reliability in this type of mechanism, because the legal tests also require that sampling is performed by a certified expert, validating the identity of the people who are asked shows and custody of samples. The DNA testing is 100% accurate when performed properly, because of its importance is necessary to ensure a strict chain of custody and results free of error through appropriate handling, process testing, and analysis of samples, that in our country, and more of these tests to be manipulated by the laboratories for personal power and economic interestsThey confuse the object and purpose of the same interest as determining paternity and maternity. A legal paternity test is conclusive evidence and legally compelling that uses DNA analysis to determine whether a man is the biological father of a child, the key to a legal paternity test is the Chain of Custody, a documentation process used the legal test to the results legally admissible, that is accepteby courts and other institutions, organizations and government agencies.